Intermittent At‐Home Suctioning of Esophageal Content for Prevention of Recurrent Aspiration Pneumonia in 4 Dogs with Megaesophagus. (2nd August 2016) - Manning, K.; Birkenheuer, A.J.; Briley, J.; Montgomery, S.A.; Harris, J.; Vanone, S.L.; Gookin, J.L.
Abstract : Background: Megaesophagus carries a poor to guarded prognosis due to death from aspiration pneumonia. Options for medical management of regurgitation are limited to strategic oral or gastrostomy tube feeding. Objectives: To describe the use and efficacy of intermittent esophageal suctioning to prevent regurgitation and associated episodes of aspiration pneumonia in dogs with megaesophagus. Animals: Four dogs with acquired idiopathic megaesophagus and recurrent aspiration pneumonia. Methods: Retrospective review of medical records of dogs with megaesophagus in which intermittent suctioning of esophageal content was employed for management of recurrent aspiration pneumonia. Results: Intermittent suctioning of the esophagus was initiated in 4 dogs after failure of strict gastrostomy tube feeding failed to prevent regurgitation and repeated episodes of aspiration pneumonia. Suctioning was accomplished by esophagostomy tube in 3 dogs and per os in 1 dog. After initiation of esophageal suctioning, dogs survived for a median of 13.5 additional months (range, 10–30 months) during which time 2 dogs had no additional episodes of aspiration pneumonia and 2 dogs had infrequent episodes of pneumonia, but aspiration was suspected to be a contributing factor in their death. Complications included clogging of the esophagostomy tube, esophagostomy site infections, and esophagitis. Conclusions and Clinical Importance: Use of intermittent esophageal suctioning in dogs with megaesophagus that continue to regurgitate despite gastrostomy tube feedings can reduce or abolish clinical episodes of aspiration pneumonia.